Prenylated flavonols from the Leaves of Macaranga gigantea (Rchb.f. & Zoll.) / M. Sulaiman M. Johari … [et al.] - M. Johari, M. Sulaiman; Ahmat, Norizan; S. Kamarozaman, Aisyah; M. Isa, M. Hamizan (UiTM Press for the Institute of Research Management & Innovation (IRMI), Universiti Teknologi MARA, 2019)
The genus Macaranga comes from the family of Euphorbiaceae and it is the only genus in the subtribe Macaranginae that have a large genus with 300 species of which 27 species were found in Peninsular Malaysia. This plant grows as shrubs or trees that can grow up to 15 m tall and known for their mutual associations with ants. Fresh or dried leaves of some Macaranga species were used by traditional healers to treat swellings, cuts, sores, boils and bruises. The isolation of chemical constituent from this genus has been shown to produce numerous results of phenolic compounds, such as flavonoids and stilbenoids. In this paper, we report the isolation of a prenylated flavonol, glyasperinA (1), together with a simple flavone apigenin (2) from the methanolic extract of the leaves of Macaranga gigantea. The structure of both compounds has been elucidated based on its spectroscopic data, including mass spectroscopy (MS), infrared (IR), ultraviolet-visible (UV-Vis), 1D and 2D nuclear magnetic resonance (NMR) spectra and comparison with the previous literature.